Effect of Telerehabilitation on Handwriting Performance in Children With Attention Deficit Hyperactivity Disorder: Randomized Controlled Trial. - Kaplan Kılıç, Büşra; Bumin, Gonca; Öğütlü, Hakan (Child: Care, Health & Development, 2025)
Background: Children with attention deficit hyperactivity disorder (ADHD) frequently encounter challenges in their fine motor skills, an area that therapists target for enhancement through therapeutic interventions. This study aimed to effect of telerehabilitation on handwriting performance in children with ADHD. Methods: In this randomized controlled trial, 70 children (33 girls and 37 boys) with ADHD aged between 6 and 8 years were randomly assigned to intervention and control groups. Fine motor skills and handwriting performance of both groups were evaluated pre–post‐intervention using the Bruininks‐Oseretsky Test of Motor Proficiency‐2nd Edition (BOT‐2) and Minnesota Handwriting Assessment (MHA) tests. The intervention group received fine motor skills training through telerehabilitation for 8 weeks, 3 days a week, 40 min each session (totalling 24 sessions). The control group was placed on a waiting list for 8 weeks and did not receive any intervention. Statistical methods analysed changes within and between groups pre–post‐intervention. Results: In the intervention group, intra‐group change pre–post‐intervention was observed in all subdomains of MHA except legibility (p < 0.05). Compared with the control group, the intervention group showed significant differences in BOT‐2 and MHA's subdomains. Discussion: The results of this study suggest that fine motor skills training through telerehabilitation may be effective in improving the handwriting performance of children with ADHD.